2015
DOI: 10.1186/s40555-014-0096-1
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Talitridae family (Crustacea, Amphipoda) in some Tunisian coastal lagoons

Abstract: Background: Although wetlands were remarkable habitats with their fauna and flora diversity, few studies have been devoted to the study of amphipod distribution in this type of environment. To study both qualitatively and quantitatively amphipod community, surveys were conducted during the spring season in ten coastal lagoons ranging from subhumid to arid bioclimatic stage. At each station, eight quadrats of 50 × 50 cm were randomly placed. Amphipods were preserved in alcohol 70°C. In the laboratory, the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In Tunisia, diversity studies of terrestrial isopod communities inhabiting the supralittoral zone of wetlands effectively started with the work of Jelassi, Khemaissia & Nasri‐Ammar (); Jelassi et al . (, ); and Khemaissia et al . (,b).…”
Section: Introductionmentioning
confidence: 96%
“…In Tunisia, diversity studies of terrestrial isopod communities inhabiting the supralittoral zone of wetlands effectively started with the work of Jelassi, Khemaissia & Nasri‐Ammar (); Jelassi et al . (, ); and Khemaissia et al . (,b).…”
Section: Introductionmentioning
confidence: 96%
“…It has a high number of habitats that are of interest from a naturalistic point of view. However, as these habitats are under increasing exploitation, estimates of lagoon biodiversity are urgent (Guelorget et al, 1982;Pergent and Zaouali, 1992;Rabaoui et al, 2014;Jelassi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…According to Williams [50], the relationship between population movements and trophic preferences does not seem to be a major parameter in the structuring of zonation despite the important mobility of the sandhopper Talitrus saltator, which would induce a greater choice of nutrient sources. Studying the biodiversity of amphipods in some coastal lagoons in Tunisia, Jelassi et al [33] showed that the most important species richness observed in the bank of Bizerte lagoon would be related to the presence of important vegetation in spring as well as…”
Section: Discussionmentioning
confidence: 99%
“…In Tunisia, amphipod communities inhabiting wetlands bank, other than sandy beaches [21][22][23][31][32][33][34][35] have not received much attention. Through this study, we propose a description as exhaustive as possible of the biodiversity of these communities taking into account geographical, climatic and edaphic specificities.…”
Section: Introductionmentioning
confidence: 99%